'Quel monstre de vice […] que la langue refuse de nommer ?': Monsters and the Politics of Naming in La Servitude volontaire (and beyond). Issue 1 (2nd January 2022) - Williams, Wes
Abstract : This discussion conjugates La Boétie's exploration of the negative valency of 'la servitude volontaire' with a set of ancient, early modern, and contemporary images and texts – from Homer and Cicero, through Montaigne and Hobbes, to Racine and Kadir Nelson. The force of ancient example is registered in the repeated haunting of the body politic by the ghost of tyranny: across genres, locations, and times, one generation after another seems to consent to the subjection of body, property, and soul to the tyrant's cause. Reworking insights and images drawn from La Servitude volontaire, political theorists and dramatists, writers, and artists bear exemplary witness to the dance by which we trace the contours, shapes, and limits of love and (be)longing, community and action, agency and will.